Air Quality in Jakarta and Management Efforts in The Context of Sustainable Development Goals: Kualitas Udara di Jakarta dan Upaya Penanganan dalam Konteks Tujuan Pembangunan Berkelanjutan (SDGs) - Saputra, Rafid Aria (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
Air quality in Jakarta has become a major concern in recent decades, given its serious impact on public health and the environment. This article describes the air conditions in Jakarta, the mitigation efforts that have been made, and their relevance to the Sustainable Development Goals (SDGs). High air pollution, especially from motor vehicle and industrial emissions, has caused an increase in concentrations of PM 2.5 particles and toxic gases such as NO2 and S02. The negative impact on public health, including respiratory disease and heart disease, is increasingly worrying. Efforts to address air quality in Jakarta have been carried out through various initiatives. The local government has tightened vehicle emission regulations, intensified the use of environmentally friendly transportation, and promoted sustainable mobility. Apart from that, greening measures and improving the waste management system are also being taken to reduce air pollution from industry. The relevance of efforts to address air quality in Jakarta with the SDGs is very important. This is related to SDGs number 3, which targets good health and prosperity for all. By reducing air pollution, Jakarta contributes to improving public health. Overall, air quality in Jakarta is an urgent issue and requires further action. The handling efforts that have been made, although positive breakthroughs, need to continue to be improved to achieve the broader SDGs goal, creating healthier and more sustainable cities for future generations.